UJI DAYA TERIMA DAN NILAI GIZI BROWNIES SINGKONG - Elvina Novyanti Pulungan; Albiner Siagian; Ernawati Nasution (Gizi, Kesehatan Reproduksi dan Epidemiologi, 2013)
Cassava is one of the food ingredients to support food diversification program. For it is necessary to introduce processed cassava product to get new food alternatives. Brownies made with cassava flour and cassava flour can add additional types of brownies that have been there in the market. This study is an experiment that is making brownies using 100% cassava flour and cassava flour addition of 50%. Panelists in this study were student school of public health University of North Sumatra as thirty people. Acceptability test data obtained were analyzed descriptively and nutritional value of carbohydrates was deretmined by hydrolysis methode and phosphor was determined by AAS method (atomic absorption spectrofotometri) and the method was tested in the laboratorty standardization agency for industrial research and medan. the results showed that student receive the test public health University of North Sumatraagainst brownies. The addition of cassava flour is preferred by the addition of 50% brownies. The addition of cassava flour in making brownies giving increasing amountd of carbohydrat and phosphor on the brownies. The addition of cassava flour in making brownies with a variety of different influence evident on the assessment test acceptability in terms of taste, aroma and texture and nutrient content of the resulting brownies. But did not give a significatly different efect on the color brownies. Then it is recommended that the public can make brownies cassava as food alternatives because it contains carbohydrates and phosphorus necessary body.Keyword : Brownies, Cassava, Nutrient Composition, Acceptability Test